Complex Stellar System ESO65SC03: Open Cluster or Remnant?. (9th June 2015) - Joshi, Gireesh C.; Joshi, Y. C.; Joshi, S.; Chowdhury, S.; Tyagi, R. K.
Abstract: We present a complete spatial and dynamical study of the poorly populated stellar system ESO65SC03. The radial distribution of the system gives a core and cluster radii of 1.10±0.63 and 5.36±0.24 arcmin, respectively. The SNDP does not show any clear enhancement of the surface stellar number density between the stars of the system and the field regions. We derive the optimum isochrone solution for a particular grid size in the CMD using the statistical cleaning procedure. Using the statistically cleaned CMDs, we find the distance modulus, ( m − M )0, and reddening, E ( B − V ), of the system to be 11.8±0.2 and 0.45 mag, respectively. The mean proper motion of this system is − 5.37±0.81 mas yr −1 and 0.31±0.40 in RA and DEC directions, respectively. The mean proper motion of this system is found to be almost similar to the field region. The mass function for the brighter stars is found to be too high for the system to be an open cluster. These combined results place constraints on whether stellar system ESO65SC03 is a POCR or an Asterism. Our understanding is that the ESO65SC03 is in a stage of POCR by losing their main-sequence stars in the dynamic evolution processes.